Pendekatan Fenomenologi dalam Studi Islam - Eni Kusrini (Halaqatuna, 2025)
Phenomenology in Islamic studies is an approach that emphasizes a deep understanding of human religious experience without being bound by specific theological, metaphysical, or philosophical frameworks. This approach focuses on how religious phenomena are present in individual consciousness, as well as how religious meaning is constructed through everyday life experiences. In the context of Islamic studies, phenomenology is used to understand religious behavior, religious institutions, and the social dynamics that accompany them in a neutral and descriptive manner. This article outlines the historical and philosophical foundations of phenomenology, beginning with Edmund Husserl as the central figure, and continuing with other figures such as Alfred Schutz, Martin Heidegger, Jean-Paul Sartre, Ernst Cassirer, John McTaggart, Wilhelm Dilthey, Jacques Derrida, and Soren Kierkegaard. Each contributed a unique perspective in developing phenomenology both as a philosophical approach and a methodology in the social sciences. Especially through Schutz, phenomenology became more applicable in social analysis, including in the study of religion. Religious phenomenology is positioned as an investigative approach to diverse religious facts, symbols, and experiences, transcending cultural and traditional boundaries. Despite facing criticism, such as from the Sophists who reject claims of universal truth, this approach offers a reflective space to engage in dialogue about faith, reason, and social context in a more open manner. Therefore, phenomenology can serve as a middle ground between philosophical and theological approaches, and open possibilities for integration with other disciplines such as psychology, anthropology, and sociology, in understanding religion as a complex human phenomenon